MENGOPTIMALKAN POTENSI LOKAL KOLANG-KALING SEBAGAI PRODUK INOVASI DI DESA PABANGBON KECAMATAN LEUWILIANG - Darmawan, Wirahadi; Anwar, Miftakhul; Lestari, Hana (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
This community service research aims to deternine the local potential of the Pabangbon Village area which cann be used as a village Innovation. This community service research was conducted in Pabangbon Village with the subject of village communities. The method used in this research is a qualitative descriptive method, namely describing a phenomenon based on what it is. This research was conducted in one of the villages in Pabangbon Village, Leuwiliang District, whit the subject being residents of Cilame Village 2. The data collection method used was observation and interviews. The data analysis technique used is phenomenological analysis. This research was carried out for approximately 1 month, starting form June 19 to August 29 2024. From the results of this research it was found tha the Pabangbon Village area has abundant natural resources so that they are used by the community to garden sugar palm trees whose seeds are processed into palm fruit. This local potential was utilized into an innovative product called Koka Chips Pabangbon.